Influence of Different Sizes of Brooding Box Made of Clay and Bamboo Basket on the Hatchability of Chicken Eggs Through Broody Hen (Progressive Agriculture, 2014)
An experiment was conducted to hatch chicken eggs in two different types of brooding boxes made of clay and bamboo basket by using broody hen. Three different size boxes were used under each type which were large(48 × 33 × 18 cm), medium (43 × 28 × 18 cm) and small (38 × 23 × 18 cm) (i.e. diameter of upper portion × diameter of lower portion × height of brooding boxes). The objective was to identify the optimum size of the brooding box used for natural hatching and to identify the appropriate material for brooding box used for incubation of eggs under rural condition. The fertility was not significantly affected by the type and size of boxes. Hatchability, Chicks not pipped and dead in germ were not significantly affected by types of boxes made of clay and bamboo basket but significantly affected by the size of boxes (p